Exploring the Challenges of Implementing Integrated Coastal Management and Achieving Sustainability within the Cameroon Coastline - Ngoran,Suinyuy Derrick (2016)
Integrated coastal management (ICM) has been accepted as a strategic management approach in achieving sustainable development in coastal areas. As such, many coastal nations, both from the developed and less developed countries have surmounted many challenges of the coastal milieu with a successful implementation of ICM and now enjoy a sound environment and a viable economy. However, a country like Cameroon with a coastline of about 402km still faces a lot of challenges in implementing ICM. According to Article 55 et seq of the Constitution, which lays down the general guidelines in matter of decentralization in Cameroon, the State is supposed to devolve upon regional and local authorities, under conditions laid down by law, powers over matters essential to their economic, social, health, educational, cultural and sports development. In reality, devolution of power still remains a nightmare, stifling sustainable coastal development. This paper, therefore, addresses the challenges faced by the State of Cameroon in implementing ICM. The work identifies predicaments/gaps in environmental planning and also makes relevant recommendations in bridging such gaps. In order to attend a desirable degree of sustainability within Cameroons coastline, real implementation of ICM can only be achieved if sectoral lines are effectively minimized through the enforcement of the decentralization process.